PERLINDUNGAN HUMAN SECURITY OLEH UPT P2TK JAWA TIMUR TERHADAP PMI NON-PROSEDURAL: STUDI KASUS PEMALSUAN PASPOR OLEH PMI ASAL Medan - Suhendra, Magna; Alfiana, Rike; Bagas S., Moch. Zharfan (Journal of Administration and International Development, 2025)
Irregular Indonesian Migrant Workers (PMI) are highly vulnerable to human security violations, including exploitation, violence, and document forgery. The case of the deportation of a migrant worker from Medan who forged a passport to work in Malaysia serves as a concrete example of this vulnerability. This study seeks to analyze the role of UPT P2TK East Java in protecting the human security of such migrant workers.This journal employs a descriptive qualitative research method, utilizing primary data through interviews and secondary data from literature, policy documents, and other relevant sources. The findings of the study indicate: (1) the complexity of human security threats that are interrelated and mutually reinforcing, including aspects of personal, food, health, and economic security; (2) UPT P2TK East Java provides holistic protection based on the dimensions of human security, such as offering safe shelters for psychological recovery, fulfilling basic needs including nutritious food, and conducting health examinations; (3) UPT P2TK East Java demonstrates comprehensive protection through an approach aligned with the principles of human security as defined by the Commission on Human Security (CHS), namely a protection strategy based on top-down approaches and cross-sectoral coordination. These findings are expected to contribute to the academic literature on the role of local governments in protecting irregular migrant workers and serve as a valuable reference for stakeholders in formulating more effective local-level approaches.